2019
DOI: 10.21037/gs.2018.11.04
|View full text |Cite
|
Sign up to set email alerts
|

Validation of molecular biomarkers for preoperative diagnostics of human papillary thyroid carcinoma in fine needle aspirates

Abstract: Background: Despite substantial efforts, reliable preoperative diagnostic for human thyroid malignancies in case of cytologically indeterminate nodules is still missing, resulting in high number of unnecessary thyroidectomies. In an attempt to increase precision of existing preoperative diagnostics, we aimed at validating the panel of molecular biomarkers predictive for papillary thyroid carcinoma (PTC) in preoperative fine needle aspirate (FNA) samples.Methods: In this prospective study conducted in preoperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 49 publications
1
20
0
Order By: Relevance
“…In the past 10 years, we have witnessed significant progress in the field of the molecular pathogenesis of thyroid carcinoma based on studies using NGS. In 2014, The Cancer Genome Atlas testing for discriminating malignancy from benignity were 63%-94% and 52%-99%, respectively, with FNB [19][20][21]. Regardless of how sensitive or specific it is, applying gene testing to FNB is limited in clinical practice because specialized sample collection is required at the time of the initial procedure.…”
Section: Results Of Ngsmentioning
confidence: 99%
“…In the past 10 years, we have witnessed significant progress in the field of the molecular pathogenesis of thyroid carcinoma based on studies using NGS. In 2014, The Cancer Genome Atlas testing for discriminating malignancy from benignity were 63%-94% and 52%-99%, respectively, with FNB [19][20][21]. Regardless of how sensitive or specific it is, applying gene testing to FNB is limited in clinical practice because specialized sample collection is required at the time of the initial procedure.…”
Section: Results Of Ngsmentioning
confidence: 99%
“…Based on their understanding of thyroid carcinoma's mutational profile, researchers have tried to use diverse molecular approaches to improve diagnosing uncertain biopsy samples and have presented various published results. The sensitivity and specificity of gene testing for discriminating malignancy from benignity were 63-94% and 52-99%, respectively, with FNB [19][20][21]. Regardless of how sensitive or specific it is, applying gene testing to FNB is inconvenient in clinical practice because specialized sample collection is required at the initial procedure.…”
Section: Discussionmentioning
confidence: 99%
“…For example, studies in human primary thyrocytes indicated that progression of papillary thyroid carcinoma is paralleled with altered synchronization properties of these cells [394]. Although causality often remains unexplored in these studies, changed expression levels of individual core clock genes have clearly been linked to the progression of oncogenic transformation, making them plausible candidates for diagnostic biomarkers [228,312,394,400,[408][409][410][411].…”
Section: Circadian Clock Perturbation and Human Diseasesmentioning
confidence: 99%
“…Today, increasing numbers of immediate clinical applications emerge from recent studies of human clocks in their physiological state, as well as under pathological conditions. Utilizing individual clock properties as molecular biomarkers holds promise for personalized medicine approaches, as well as for diagnostic purposes [372,408,432]. Chronopharmacology that takes into account circadian pharmacokinetics and pharmacodynamics already plays an important role for a number of medications widely used for treating oncological, metabolic, and respiratory diseases [433,434].…”
Section: Perspectivesmentioning
confidence: 99%